Increased rate of abdominal surgery both before and after diagnosis of celiac disease. Issue 2 (February 2017) - Kurien, Matthew; Sanders, David S.; Ekbom, Anders; Ciacci, Carolina; Ludvigsson, Jonas F.
Abstract: Background: The detection of celiac disease (CD) is suboptimal. Aims: We hypothesized that misdiagnosis is leading to diagnostic delays, and examine this assertion by determining if patients have increased risk of abdominal surgery before CD diagnosis. Methods: Through biopsy reports from Sweden's 28 pathology departments we identified all individuals with CD (Marsh stage 3; n = 29, 096). Using hospital-based data on inpatient and outpatient surgery recorded in the Swedish Patient Register, we compared abdominal surgery (appendectomy, laparotomy, biliary tract surgery, and uterine surgery) with that in 144, 522 controls matched for age, sex, county and calendar year. Conditional logistic regression estimated odds ratios (ORs). Results: 4064 (14.0%) individuals with CD and 15, 760 (10.9%) controls had a record of earlier abdominal surgery (OR = 1.36, 95% CI = 1.31–1.42). Risk estimates were highest in the first year after surgery (OR = 2.00; 95% CI = 1.79–2.22). Appendectomy, laparotomy, biliary tract surgery, and uterine surgery were all associated with having a later CD diagnosis. Of note, abdominal surgery was also more common after CD diagnosis (hazard ratio = 1.34; 95% CI = 1.29–1.39). Conclusions: There is an increased risk of abdominal surgery both before and after CD diagnosis. Surgical complications associated with CD may best explain these outcomes. Medical nihilism and lack of CD awareness may be contributing to outcomes.